ANALISIS KEMAMPUAN KEUANGAN PEMERINTAH DAERAH KOTA PALU DALAM MEMBIAYAI PENGELUARANNYA - Rusman, Liswan (Katalogis, 2018)
The research is aimed to determine and analyze: 1) the development of local revenue sources; 2) the capacity of local revenue acceptance; 3) the capacity of local revenue in financing of Palu City; 4) Financial capacity of local Palu government based on regulation of the ministry of Domestic Affairs no. 21, 2007; 5) the leve of fiscal decentralization in financing the expenditure of Palu City; 6) fiscal capacity of Palu government; 7) the capacity of the local revenue to repay local debats. This study is descriptive. Data is collected through interview, literature review, and analysis of Palu government’s financial document. The results show that: 1) the development of local revenue sources indicates that other legitimate of local revenue has the highest growth and contribution of 226.08% and 40.92%; 2) the capacity of local revenue is classified ‘deficient’; 3) the capacity of local revenue is financing expenditure is categorized ‘unable to pay the expenditure’; 4) financial capacity of local Palu government based on the regulation of The Ministry of Domestic Affairs no. 21, 2007 is categorized in ‘low’ and medium’ financial groups; 5) the leve of fiscal decentralization in financing the expenditure of Palu City is still unable to finance the local expenditure; 6) fiscal capacity of Palu government in 2011-2013 budget year in categorized ‘low’ and ‘medium’ in 2014-2015; 7) DSCR ratio shows the capacity of Palu Government to repay local debts.